Why I hate Abercrombie & Fitch : essays on race and sexuality - McBride, Dwight A. (Sexual cultures., 2005)
Why hate Abercrombie? In a world rife with human cruelty and oppression, why waste your scorn on a popular clothing retailer? The rationale, Dwight A. McBride argues, lies in "the banality of evil," or the quiet way discriminatory hiring practices and racist ad campaigns seep into and reflect malevolent undertones in American culture. McBride maintains that issues of race and sexuality are often subtle and always messy, and his compelling new book does not offer simple answers.